2014
DOI: 10.1080/10242694.2014.886432
|View full text |Cite
|
Sign up to set email alerts
|

Military expenditure, economic growth and structural instability: a case study of South Africa

Abstract: This paper makes two contributions to the growing literature on the military expenditureeconomic growth nexus. It provides a case study of a developing country, South Africa, and considers the possibilities of structural breaks in the relationship, applying newly developed econometric methods. Taking annual data from 1951 to 2010 and full sample bootstrap Granger non-causality tests, initially we find no causal link between military expenditure and GDP. Then, using parameter instability tests, the estimated VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…. , T and calculate the bootstrap p-values using the residual based method explained in the appendix to [36] for the two null hypotheses (a) that M2GDP does not Granger cause RGDPPC and (b) that RGDPPC does not Granger cause M2GDP. More precisely, the residual based p-values of the modified LR-statistics that tests the absence of Granger causality from M2GDP to RGDPPC or vice-versa is computed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…. , T and calculate the bootstrap p-values using the residual based method explained in the appendix to [36] for the two null hypotheses (a) that M2GDP does not Granger cause RGDPPC and (b) that RGDPPC does not Granger cause M2GDP. More precisely, the residual based p-values of the modified LR-statistics that tests the absence of Granger causality from M2GDP to RGDPPC or vice-versa is computed.…”
Section: Resultsmentioning
confidence: 99%
“…The results of Granger causality tests based on the full sample also become invalid with structural breaks because they assume parameter stability. Therefore, this study tests for parameter stability in the estimated VAR models following [34]- [36]. In practice, a number of tests exist for examining the temporal stability of VAR models [39]- [41].…”
Section: Data and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors further MCSER Publishing, Rome-Italy Vol 5 No 20 September 2014 2771 suggested that the military expenditure of the apartheid system did have a bad effect on the growth of South Africa. Another study conducted in South Africa was that of Aye, Balcilar, Dunne, Gupta and van Eyden (2013) found that at 5 percent significant level no cointegration between GDP and military expenditure. Their study only applied the techniques of Johansen cointegration.…”
Section: Literature Surveymentioning
confidence: 99%
“…Focusing on the supply side approach, the neoclassical view states that economic activities are affected by military spending through the factors such as infrastructure originating externalities, technological spin-off, human capital etc. On the other hand, the Keynesian view focuses on the demand side approach and argues that military spending affects economic growth through the crowding-out effect and fields such as export, education and health (Karagol & Palaz, 2004;Yildirim et al, 2004;Aye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%